2020
DOI: 10.1242/dmm.045369
|View full text |Cite
|
Sign up to set email alerts
|

A novel mouse model of Duchenne muscular dystrophy carrying a multi-exonic Dmd deletion exhibits progressive muscular dystrophy and early-onset cardiomyopathy

Abstract: Duchenne muscular dystrophy (DMD) is a life-threatening neuromuscular disease caused by the lack of dystrophin, resulting in progressive muscle wasting and locomotor dysfunctions. By adulthood, almost all patients also develop cardiomyopathy, which is the primary cause of death in DMD. Although there has been extensive effort in creating animal models to study treatment strategies for DMD, most fail to recapitulate the complete skeletal and cardiac disease manifestations that are presented in affected patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 70 publications
(92 reference statements)
2
25
0
Order By: Relevance
“…Our analyses showed that DMD CMs have structural, morphological, and functional defects including larger surface areas, lower cell volumes and shorter sarcomere lengths, consistent with data from in vivo and in vitro models of DMD and dilated cardiomyopathy. 37,49,51,52,70 Further, our contractility analyses demonstrated systolic and diastolic dysfunction in DMD CMs, in line with clinical findings in DMD patients 53 and a previous iPSC model of DMD-associated cardiomyopathy. 51 Dystrophin functions as an intermediary between membrane and cytoskeleton biology, and it is known that the lack of dystrophin in DMD results in cytoskeletal disruptions, such as microtubule dysregulation and increased cytoskeletal stiffness, 71 as well as abnormalities in plasma membrane structure and function resulting in calcium overload.…”
Section: Discussionsupporting
confidence: 89%
“…Our analyses showed that DMD CMs have structural, morphological, and functional defects including larger surface areas, lower cell volumes and shorter sarcomere lengths, consistent with data from in vivo and in vitro models of DMD and dilated cardiomyopathy. 37,49,51,52,70 Further, our contractility analyses demonstrated systolic and diastolic dysfunction in DMD CMs, in line with clinical findings in DMD patients 53 and a previous iPSC model of DMD-associated cardiomyopathy. 51 Dystrophin functions as an intermediary between membrane and cytoskeleton biology, and it is known that the lack of dystrophin in DMD results in cytoskeletal disruptions, such as microtubule dysregulation and increased cytoskeletal stiffness, 71 as well as abnormalities in plasma membrane structure and function resulting in calcium overload.…”
Section: Discussionsupporting
confidence: 89%
“…In recent years, other DMD mouse models recapitulating patient‐specific deletions have been generated. These models carry deletions of DMD exons, including single (Amoasii et al, 2017; Young et al, 2017; Min et al, 2019a; Min et al, 2020) and multi‐exonic deletions (Egorova et al, 2019; Wong et al, 2020). Concerning duplication mutations, the only model previously available was Dup2 (Vulin et al, 2015) harboring a single exon duplication of Dmd exon 2.…”
Section: Discussionmentioning
confidence: 99%
“…This feature is not well‐recapitulated in mdx mice, which generally start showing a mild cardiac phenotype in late stage of disease (Chu et al, 2002; Quinlan et al, 2004; Au et al, 2011). More recently, the Dmd ΔEx52‐54 mouse model was the first to show an early onset dystrophic cardiac phenotype and cardiac functional abnormalities that closely recapitulate the human disease (Wong et al, 2020). Further analysis in the Dup18‐30 mouse model would be required to assess cardiac function and investigate progression of disease manifestations in late disease stages.…”
Section: Discussionmentioning
confidence: 99%
“…Dystrophic mouse models, notably a series of mdx models, are valuable tools in the proof-of-concept stages of drug candidates because the strains have been established and well characterized. Novel dystrophic models with mice and rats are also further along in development utilizing their facility for genetic manipulation [ 45 , 46 , 47 ]. On the other hand, canine models of GRMD and CXMD J have played pivotal roles in DMD research, as they display many of the clinical manifestations seen in patients.…”
Section: Discussionmentioning
confidence: 99%